Analisis Pengaruh Debt To Equity Ratio (DER) dan Return On Equity Terhadap Price To Book Value (PBV) - Citra Amelia, Yunika; Rakhmat; Sugiyanta, Yohanes (Mulia Pratama, 2024)
This study aims to see the effect of debt to equity ratio and return on equity on price to book value. The population of this study was 92 companies in the property and real estate sector listed on the Indonesia Stock Exchange for the 2020-2022 period, which were selected using the purposive sampling method. Then, 14 companies were selected as research samples. The data processed is secondary data in the form of annual financial reports with a quantitative approach. The analysis technique used is multiple linear regression using the Eviews 12 application, with several tests, namely descriptive statistical analysis, estimation model determination test, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of the study show that first, partially the debt to equity ratio has a positive and significant effect on price to book value. The debt to equity ratio produces a regression coefficient of 1.860377. Tcount is 6.354173 is greater than Ttable (6.354173 > 1.974271) with a probability of 0.0000 < 0.05. Second, partially return on equity has a positive and significant effect on price to book value. Return on equity produces a regression coefficient of 3.813042. Tcount is 3.228050 is greater than Ttable (3.228050 > 1.974271) with a probability of 0.0015 < 0.05. Third, simultaneously debt to equity ratio and return on equity have a significant effect on price to book value. Fcount is 5.627726 is greater than Ftable (5.627726 > 3.05012) with a probability of 0.0000 < 0.05. Furthermore, the R2 value is 0.357065, meaning that the debt to equity ratio and return on equity are able to explain the price to book value by 35.70%, while the remaining 64.30% is influenced by other factors outside this research model.